2004
DOI: 10.1016/j.cardiores.2003.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Aging-related induction of inducible nitric oxide synthase is vasculo-protective to the arterial media

Abstract: These observations suggest that ED and arteriosclerosis in the aging male may share a common etiology, and that the expression of iNOS by the SMC is an attempt to counteract this fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
87
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 41 publications
12
87
0
1
Order By: Relevance
“…3). This results suggest an enhanced oxidative stress in VSMCs from the late-passages which is consistent with the previous reports [21,35]. However, IGF-1 exposure (10 ng/ml) failed to enhance ROS formation in cells from either the early or late passages.…”
Section: Migration and Proliferation Of Different Passage Vsmcssupporting
confidence: 93%
“…3). This results suggest an enhanced oxidative stress in VSMCs from the late-passages which is consistent with the previous reports [21,35]. However, IGF-1 exposure (10 ng/ml) failed to enhance ROS formation in cells from either the early or late passages.…”
Section: Migration and Proliferation Of Different Passage Vsmcssupporting
confidence: 93%
“…Studies on liver and kidney fibrosis in the iNOS knock-out mouse, and our previous work in Peyronie's disease and its animal models, vaginal fibrosis, aging-related arterial media fibrosis, and in corporal fibrosis, suggests that despite iNOS may be initially induced during an early inflammatory process, its main role is as an antifibrotic agent. 12,13,[24][25][26][27][28][29]32,33,37,38,50 This may occur via cGMP produced by the nitric oxide from iNOS, and/or the nitric oxide can directly reduce collagen synthesis, myofibroblast formation in the interstitial connective tissue, and reactive oxygen species. 26,[30][31][32] In contrast to our study with vardenafil in the BCNR rat, the slight stimulation of iNOS induction by sildenafil in the BCNR animals was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23] The expression of iNOS in certain non-immunological tissues is assumed to be a defense mechanism against fibrosis. [24][25][26][27][28][29] The nitric oxide produced by iNOS, besides inhibiting collagen synthesis and the TGFb1 pathway, also quenches reactive oxygen species, and in some cases, the differentiation of fibroblasts to myofibroblasts, the cells that produce collagen in many fibrotic conditions. [30][31][32] In a recent study, we have shown that the PDE5 inhibitor, vardenafil, given for 45 days in the drinking water to rats subjected to bilateral cavernosal nerve resection (BCNR) [33][34][35] prevented the development of CVOD and the underlying SMC loss and fibrosis in the corpora cavernosa.…”
Section: Introductionmentioning
confidence: 99%
“…12 For this reason we included in the analysis the variable 'age' that was found to be directly related to the presence of CCAD (Figure 3) and ED. This analysis showed that age influenced significantly the PSV cut-off values.…”
Section: Discussionmentioning
confidence: 99%